"Encephalopathy Only Stroke Codes" (EoSC) Rarely Result in Stroke as Final Diagnosis. (11th February 2019) - Chen, Patrick M.; Meyer, Dawn M.; Claycomb, Robert; Agrawal, Kunal; Meyer, Brett C.
Abstract : Stroke codes prompted by isolated encephalopathy often result in nonstroke final diagnoses but require intensive stroke center resources. We assessed the likelihood of "Encephalopathy only Stroke Codes (EoSC)" resulting in a true stroke (EoSC CVA+) final diagnosis. 3860 patients were analyzed in a prospective stroke code registry from 2004 to 2016. EoSC was defined using a standard and an exploratory definition. Definition 1 included EoSC patients as stroke codes where NIHSS was nonzero for LOC questions (questions la, 1b, and lc) but remainder of the NIHSS was zero. Definition 2 included the same definition but allowed symmetric pairings on motor questions (5a/5b, 6a/6b, or Question 4 scoring a 3). Groups were assessed for final diagnosis of stoke (EoSC CVA+) or not stroke (EoSC CVA-). EoSC accounted for 60/3860 (1.55%) of total stroke codes. EoSC CVA+ was found in 5/3860 (0.13%) of all stroke codes, 5/60 (8.33%) of EoSC stroke codes, and 5/1514 (0.33%) of all strokes. For Definition 2, EoSC accounted for 96/3860 (2.5%) of total stroke codes. EoSC CVA+ was found in 9/3860 (0.23%) of all stroke codes, 9/96 (9.38%) of EoSC stroke codes, and 9/1514 (0.59%) of all strokes. On multivariable logistic regression analysis, diabetes was the highest predictor of stroke (p=0.05). Encephalopathy only Stroke Codes only rarely result in cases with a true final diagnosis of stroke (EoSC CVA+), accounting for 0.1-0.2% of all stroke codes and 8-9% of EoSC stroke codes. This may have important significance for mobilization of limited acute stroke code resources in the future.